2017
DOI: 10.14202/vetworld.2017.672-678
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different concentrations of soybean lecithin and virgin coconut oil in Tris-based extender on the quality of chilled and frozen-thawed bull semen

Abstract: Aim:The objective of this study was to evaluate the effects of different concentrations of soybean lecithin (SL) and virgin coconut oil (VCO) in Tris-based extender on chilled and frozen-thawed bull semen quality parameters.Materials and Methods:A total of 24 ejaculates were collected from four bulls via an electroejaculator. Semen samples were diluted with 2% VCO in Tris-based extender which consists of various concentrations of SL (1, 1.25, 1.5, and 1.75%). A 20% egg yolk in Tris used as a positive control (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 36 publications
1
18
1
4
Order By: Relevance
“…E. longifolia Jack effect as an aphrodisiac by consumption was earlier described [ 52 ]. Soybean and egg-yolk based extender has long been established in semen cryopreservation [ 53 ]. Study in Eurycoma longifolia has been initiated and revealed cryopreservative effect in bull spermatozoa [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…E. longifolia Jack effect as an aphrodisiac by consumption was earlier described [ 52 ]. Soybean and egg-yolk based extender has long been established in semen cryopreservation [ 53 ]. Study in Eurycoma longifolia has been initiated and revealed cryopreservative effect in bull spermatozoa [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The procedure was carried out as described by Tarig et al. (). In this procedure, semen samples were diluted at room temperature in a two‐step process with a Tris‐based extender composed of two fractions containing 7% glycerol.…”
Section: Methodsmentioning
confidence: 99%
“…In slow freezing, the temperature is gradually reduced in a stepwise manner during cryopreservation process (Mphaphathi, Luseba, Sutherland, & Nedambale, 2012). The procedure was carried out as described by Tarig et al (2017). In this procedure, semen samples were diluted at room temperature in a two-step process with a Trisbased extender composed of two fractions containing 7% glycerol.…”
Section: Slow Freezingmentioning
confidence: 99%
“…Nilai MPU semen sapi bali dalam penelitian ini (60-68%) berbeda dengan nilai MPU sapi Jantan di Malaysia (59%-72%) (Tarig et al, 2017). Perbedaan ini kemungkinan disebabkan oleh jenis pengencer dan jenis ternak yang berbeda, serta teknik penampungan yang digunakan berbeda (Arifiantini & Purwantara, 2010).…”
Section: Membran Plasma Utuh (Mpu)unclassified